REPRODUCTION HUMAN CAPITAL - Xoshimova Sevara Bakhromovna (Journals Park Publishing, 2023)
This article shows the relationship between investment in education, human capital development, and employment, and shows the important role of human capital reproduction in economic growth and development.
Keywords: human capital, reproduction of human capital, formation, exchange, distribution.